1999
DOI: 10.1159/000028875
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Pseudocysts Complicating CSF Shunting in Infants and Children

Abstract: Abdominal pseudocysts (APC) are rare complications of ventriculoperitoneal shunting for hydrocephalus. The authors studied retrospectively a series of 18 pediatric patients with APC. Signs and symptoms of shunt dysfunction were observed in 15 (83.3%), abdominal complaints in 10 (55.5%) and fever in 6 (33.3%). Prior to the diagnosis of APC, 2 patients suffered exploratory laparotomies due to important abdominal signs and symptoms. Ultrasonography was diagnostic in all cases and proved to be the method of choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 31 publications
0
73
0
Order By: Relevance
“…In literature, it is seen that laparoscopy procedures are favored in the recent years [10]. In the presence of an infection, it is suggested that implanting an external ventricular drain and installing a new shunt after appropriate antibiotherapy and seeing CSF is sterile [2,4,8]. In our cases we saw that, sending the catheter to a different quadrant, without excision of the pseudocysts, is sufficient.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In literature, it is seen that laparoscopy procedures are favored in the recent years [10]. In the presence of an infection, it is suggested that implanting an external ventricular drain and installing a new shunt after appropriate antibiotherapy and seeing CSF is sterile [2,4,8]. In our cases we saw that, sending the catheter to a different quadrant, without excision of the pseudocysts, is sufficient.…”
Section: Discussionmentioning
confidence: 56%
“…It is characterized with a cystic mass encircled with a fibrous wall with CSF and the shunt catheter inside [4]. One of the theories about the abdominal pseudocyst etiology is the inflammation theory, which proposes the main reason as recurrent infections, shunt revisions, intestinal adhesions and peritonitis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When literature was investigated, abdominal complications are; distal catheter migration and visceral perforation and/or extrusion (1,3,5,6, 11, 12, 14, 15, 17-21, 23, 24, 29-31), ascitis (2,13], and peritoneal pseudocysts (10,26). However when this literature was analyzedin detail nearly all of them are related with "non-functional" abdominal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that more than 44% of the patients with distal VPS complications had multiple abdominal revisions due to APC or peritonitis and end up as VAS candidates 3,11,21 .…”
Section: Discussionmentioning
confidence: 99%